Penerapan Nilai Nilai Islam Dalam Pembentukan Sikap Kewarganegaraan Mahasiswa - Fatimah Azzahra; Syamzaimar Syamzaimar (CV. SINAR HOWUHOWU, 2026)
This study is motivated by the decline in students’ civic character in the digital era, marked by weakened communication ethics, reduced social concern, and limited tolerance in campus and community life. These conditions show the importance of integrating Islamic values as a foundation for forming civic character aligned with Pancasila and social life in Indonesia. The purpose of this study is to analyze the application of Islamic values in shaping students’ civic attitudes based on relevant literature. This research uses a qualitative method with a library research approach. Data were collected from scholarly journals, books, and academic documents discussing the integration of Islamic values, civic education, religious moderation, and students’ character development. The data collection technique was documentation and literature review, while data analysis used content analysis and critical descriptive analysis. The findings show that the value of adab plays a role in shaping polite communication, the value of maslahah encourages concern for the public good, and the value of tasamuh strengthens tolerance in diversity. In addition, the internalization of Islamic values through learning activities, student organizations, and campus academic culture supports the formation of students who are polite, participative, and responsible as citizens. In conclusion, Islamic values have strong effectiveness in strengthening students’ civic character because they are compatible with Pancasila and support the creation of good citizenship in the modern era.